Platelets and galectins - Schattner, Mirta Ana (2014)
A major function of platelets is keeping the vascular system intact. Platelet activation at sites of vascular injury leads to the formation of a hemostatic plug. Activation of platelets is therefore crucial for normal hemostasis; however, uncontrolled platelet activation may also lead to the formation of occlusive thrombi that can cause ischemic events. Although they are essential for proper hemostasis, platelet function extends to physiologic processes such as tissue repair, wound remodeling and antimicrobial host defense, or pathologic conditions such as thrombosis, atherosclerosis, chronic inflammatory diseases and cancer. Platelets can be activated by soluble molecules including thrombin, thromboxane A2 (TXA2), adenosine diphosphate (ADP), serotonin or by adhesive extracellular matrix (ECM) proteins such as von Willebrand factor (vWF) and collagen. Here we describe recent advances in the activation of platelets by non-canonical platelet agonists such as galectins. By acting either in soluble or immobilized form, these glycan-binding proteins trigger all platelet activation responses through modulation of discrete signaling pathways. We also offer new hypotheses and some speculations about the role of platelet-galectin interactions not only in hemostasis and thrombosis but also in inflammation and related diseases such as atherosclerosis and cancer.